Local Food Potentials and Agroecology in Yogyakarta Special Province, Indonesia - Dodi Widiyanto (Forum Geografi, 2019)
This paper attempts to unveil the hidden potential of the local food through local food mapping, drawing local food potential based on the “triple burden” theory from Professor Moerdijati Gardjito. An index, called “index of food relocalisation” is adopted and then modified into different name called local food index due to data availability, which is expected to provide a geographical location of the local food potential by proposing a research questions: where do the local food potentials distribute in Yogyakarta Special Province, and why the local food potentials located in that particular area(s)? The findings show that Gunungkidul and Kulonprogo are two potential regencies with their local food crops availabilities This finding is accompanied by an explanation from the analysis from the agroecological subzone and spatial income distribution of paddy and second crops, production activities.